IMPLEMENTASI PRINSIP-PRINSIP PERTANIAN BERKELANJUTAN OLEH PETANI DI KABUPATEN KULON PROGO - Untari, Dyah Woro; Wastutiningsih, Sri Peni; Irham, Irham (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2007)
The objectives of this study are: (1) to investigate farmers comprehension on sustainable agriculture principles comprehension, (2) to identify factors that affect farmers expectancy on the advantage of sustainable agriculture, (3) to investigate farmers sustainable agriculture principles implementation, and (4) to analyze factors affecting the implementation of sustainable agriculture principles by the farmers.The total samples were 60 farmers, 30 farmers were selected from wetland ecosystem and another 30 farmers were selected from coastal ecosystem. Those 60 samples were taken by simple random sampling method. Multiple linear regression and independent sample t test techniques used in analyzing the data.The result shows that farmers have less comprehension on most of the sustainable agriculture principles especially on eco-agriculture principle. The cultural appropriateness principle comprehension affects farmers expectancy on the advantage of sustainable agriculture significantly. The implementation level of sustainable agriculture in wetland ecosystem is higher than that of in coastal ecosystem. Farmers expectancy affects sustainable agriculture implementation significantly.